2022
DOI: 10.2147/cmar.s341466
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Choice of Neoadjuvant Chemotherapy for HER2-Negative Breast Cancer: Clinical Insights

Abstract: The neoadjuvant setting provides immense opportunities for translational research and drug development. The acceptance of pathological complete response (pCR) as a surrogate endpoint for clinical benefit has led to the widespread use of neoadjuvant treatment. Optimal neoadjuvant therapies are determined based on their ability to achieve the highest rates of pCR. Predicted rates of pCR for triple negative breast cancer (TNBC) treated with sequential taxane/anthracycline regimens range from 35% to 48%. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Though it is accepted that pCR is a relevant surrogate outcome in BC literature after NAC, the relation between pCR and hard outcomes is not completely clear. Interestingly, the KEYNOTE-522 trial (triple negative NAC eligible population) suggested a high pCR rate (around 60%) in patients receiving pembrolizumab [ 18 ]. This information might reinforce the association of HER2-expressing cells with poorer outcomes, likewise reported in other HER2-positive studies in women with BC that received trastuzumab as NAC (38% pCR rate) [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though it is accepted that pCR is a relevant surrogate outcome in BC literature after NAC, the relation between pCR and hard outcomes is not completely clear. Interestingly, the KEYNOTE-522 trial (triple negative NAC eligible population) suggested a high pCR rate (around 60%) in patients receiving pembrolizumab [ 18 ]. This information might reinforce the association of HER2-expressing cells with poorer outcomes, likewise reported in other HER2-positive studies in women with BC that received trastuzumab as NAC (38% pCR rate) [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For high-risk, ER+, HER2− BC, standard adjuvant anthracycline-taxane regimens are appropriate when neoadjuvant chemotherapy is chosen. However, optimal hormone therapy is the standard of care in the adjuvant setting, whether or not a pathological complete response is obtained [ 78 ]. Tamoxifen is commonly used in the treatment of luminal BC.…”
Section: Discussionmentioning
confidence: 99%
“…With the addition of a platinum agent, pCR rates of 55% are predicted. Further increases have been observed with the addition of immune checkpoint inhibitors to this standard chemotherapy backbone (44). In the pivotal KEYNOTE-522 clinical trial, pCR rates of 65% and 69% were reported for chemotherapy plus pembrolizumab in the overall and PD-L1-positive subgroups, respectively (45).…”
Section: Neoadjuvant Therapymentioning
confidence: 99%